The use of Airborne Spectrometric Data in Geological Mapping and Uranium Exploration at Qena-Quseir Shear Zone Area, Eastern Desert, Egypt. (Global Journal of Science Frontier Research, 2017)
Qena-Quseir shear zone area is located at the central part of the Eastern Desert covering area of about 9460 Km 2 . This area is mainly covered by basement rocks however there are parts covered by sedimentary rocks ranging in age from Upper Cretaceous to Quaternary. In this research, airborne gamma-ray spectrometric data is used to refinement of the mapped surface geology depending on the radioelements content between lithological assemblages. The gamma-ray data is also used for studying the distribution of the radioactive elements and determination of anomalous zones of uranium. The data were collected by Aeroservice department, Western geophysical company of America along flight lines oriented in a NE-SW direction with 1.5 Km line spacing and along tie lines oriented in NW-SE direction with 10 Km line spacing. Radioelements maps shows three levels of concentrations. The high level is related to younger granite, Duwi formation and some parts of Dokhan volcanics whereas the lowest level is related to metavolcanics.
Keywords: gamma-ray data; radioactive elements; arithmetic mean values; interpreted radiometric lithologic unit